Modified resin composition, prepreg, laminate and printed circuit board

By modifying the reasonable compatibility of allylbenzooxazine prepolymer with other resins and fillers, the problem of large thermal expansion coefficient of the existing resin composition is solved, and a resin composition with low thermal expansion coefficient, low dielectric properties and high heat resistance is achieved, which is suitable for high-performance electronic substrates.

CN116023753BActive Publication Date: 2025-03-04GUANGDONG HINNO TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211705056.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2025-03-04
Estimated Expiration
2042-12-29

AI Technical Summary

Technical Problem

The existing electronic substrate resin composition has a large thermal expansion coefficient during multi-layer board operation, which affects the preparation process and performance.

Method used

Modified allylbenzooxazine prepolymer is used as the main component of the resin composition, and resin compositions with low thermal expansion coefficient, low dielectric constant, low dielectric loss and high heat resistance are prepared through reasonable compatibility with other resins and fillers.

Benefits of technology

The resin composition has achieved low thermal expansion coefficient, low dielectric performance and high heat resistance, and is suitable for high-performance printed circuit boards and integrated circuit packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004026047190000021
    Figure BDA0004026047190000021
  • Figure BDA0004026047190000022
    Figure BDA0004026047190000022
  • Figure BDA0004026047190000031
    Figure BDA0004026047190000031
Patent Text Reader

Abstract

The present invention discloses a modified resin composition, a prepreg, a laminate and a printed circuit board. The modified resin composition comprises, by mass, 20 to 60 parts of a modified allylbenzoxazine prepolymer, 10 to 30 parts of a curing agent, 10 to 30 parts of a functional resin, 10 to 50 parts of an inorganic filler, 5 to 20 parts of a flame retardant and 1 to 10 parts of a curing accelerator. The modified resin composition of the present invention adopts a modified allylbenzoxazine prepolymer, which reduces the steric hindrance of the modified resin composition, increases the crosslinking density, reduces the thermal expansion coefficient of the material, and improves the heat resistance; and the synergistic flame retardant effect of fluorine and nitrogen in the prepolymer enables the modified resin composition to achieve the UL94V0 flame retardant grade by adding a small amount of flame retardant, avoiding the negative impact of traditional addition of a large amount of flame retardant on the material; furthermore, the modified allylbenzoxazine prepolymer is reasonably compatible with the remaining raw material components, so that the modified resin composition has a low thermal expansion coefficient, low dielectric properties, high heat resistance and high flame retardancy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of resin materials, in particular to a modified resin composition, a prepreg, a laminate and a printed circuit board. Background Art

[0002] As electronic products develop towards being lighter, thinner, shorter, smaller, more functional and safer, electronic components are required to have higher signal propagation speed and transmission efficiency. Therefore, the substrate of the circuit board is required to have the characteristics of high heat resistance, peeling resistance, low water absorption, low dielectric constant and low dielectric loss value. At the same time, in order to achieve more functions, the number of substrate application layers is getting higher and higher, and high-layer applications also require the substrate to have both low expansion coefficient and high heat resistance.

[0003] Benzoxazine resin is a new type of phenolic resin. It is a type of intermediate containing a heterocyclic structure synthesized from phenolic compounds, aldehydes and amine compounds. It undergoes ring-opening polymerization under heating and / or the action of a catalyst to generate a nitrogen-containing network similar to phenolic resin. Since benzoxazine resin has good heat resistance and water absorption, it is often used in the preparation of electronic substrates.

[0004] A study has provided a resin composition that uses a material containing a benzoxazine prepolymer to reduce the dielectric constant and dielectric loss of the product. However, the thermal expansion coefficient of the product is relatively large, which is not conducive to the production of multilayer boards.

[0005] Therefore, how to obtain an electronic substrate resin composition having a relatively low thermal expansion coefficient, a low dielectric constant, a low dielectric loss and a high heat resistance is an urgent problem to be solved by those skilled in the art. Summary of the invention

[0006] Based on this, the main purpose of the present invention is to provide a modified resin composition having low thermal expansion coefficient, low dielectric constant, low dielectric loss and high heat resistance, as well as a prepreg and a laminate prepared from the modified resin composition.

[0007] The first aspect of the present application provides a modified resin composition, characterized in that it comprises the following components in parts by mass:

[0008]

[0009] In some embodiments, the raw materials for preparing the modified allylbenzoxazine prepolymer include allylbenzoxazine resin and allyl compound.

[0010] In some embodiments, the mass ratio of the allylbenzoxazine resin to the allyl compound is 100:(50-100), preferably 100:70.

[0011] In some embodiments, the structure of the allylbenzoxazine resin includes an allyl-type benzoxazine, and the allyl-type benzoxazine is selected from one or more of the following structures:

[0012]

[0013] Wherein, X is selected from -CHR1-, -CR2R3-, -SO2- or -O- or DCPD ring;

[0014] R1, R2, and R3 are each independently selected from -H or -CH3.

[0015] In some embodiments, the allyl compound includes a first allyl compound, and the first allyl compound is 2,2-bis(4-allyloxyphenyl)hexafluoropropane.

[0016] In some embodiments, the allyl compound includes a first allyl compound and a second allyl compound, and the second allyl compound is selected from one or more of diallyl bisphenol A, diallyl bisphenol S, diallyl bisphenol F, and bisphenol A bisallyl ether.

[0017] In some embodiments, the method for preparing the modified allylbenzoxazine prepolymer comprises the following steps:

[0018] The allyl compound and the allylbenzoxazine resin are mixed and reacted at 100° C. to 150° C. for 60 min to 120 min to obtain a modified allylbenzoxazine prepolymer. Preferably, the reaction temperature is 110° C. to 130° C. and the reaction time is 80 min to 100 min; more preferably, the reaction temperature is 120° C. and the reaction time is 90 min.

[0019] In some embodiments, the modified resin composition includes the following components in parts by mass:

[0020]

[0021] In some embodiments, the curing agent is selected from one or more of phenolic resin, dicyandiamide, diaminodiphenyl sulfone, diaminodiphenyl ether, diaminodiphenylmethane, cyanate resin, active ester, anhydride curing agent, benzoxazine, bisphenol, monophenol, polyhydroxyphenol, and hydroquinone. Preferably, cyanate resin is selected.

[0022] In some embodiments, the functional resin is selected from one or more of epoxy resin, benzoxazine resin, polyphenylene ether resin, hydrocarbon resin and bismaleimide resin, preferably epoxy resin and bismaleimide resin.

[0023] In some embodiments, the inorganic filler is selected from one or more of zirconium vanadate, zirconium tungstate, hafnium tungstate, microcrystalline glass, eucryptite, spherical silica, composite silica, fused silica, quartz, mica powder, titanium dioxide, magnesium oxide, magnesium hydroxide, talc, aluminum oxide, silicon carbide, boron nitride, aluminum nitride, molybdenum oxide, barium sulfate, zinc molybdate, zinc borate, zinc stannate, zinc oxide, strontium titanate, barium titanate, calcium titanate, clay, and kaolin. Spherical silica is preferred.

[0024] In some embodiments, the flame retardant is selected from one or more of decabromodiphenylethane, tetrabromobisphenol A, brominated epoxy resin, phosphorus-containing epoxy resin, phosphorus-containing phenolic resin, phosphazene compound, phosphate compound, phosphorus-containing cyanate, and phosphorus-containing benzoxazine.

[0025] In some embodiments, the curing accelerator is selected from one or more of tertiary amine accelerators, imidazole accelerators, peroxide accelerators, organic phosphorus accelerators and transition metal carboxylate accelerators.

[0026] The second aspect of the present application provides the use of the modified resin composition in integrated circuit packaging and printed circuit boards.

[0027] The third aspect of the present application provides a prepreg, comprising a reinforcing material and a resin material loaded on the reinforcing material, wherein the resin material is the modified resin composition mentioned above.

[0028] In some embodiments, the reinforcing material is selected from inorganic fiber materials or organic fiber materials. Inorganic fiber materials include but are not limited to glass fiber, carbon fiber, silicon carbide fiber and asbestos fiber. Organic fiber materials include but are not limited to nylon, ultra-high molecular weight polyethylene fiber, aramid fiber, polyimide fiber, polyester fiber and cotton fiber.

[0029] A fourth aspect of the present application provides a laminate, wherein raw materials for preparing the laminate include the above-mentioned prepreg.

[0030] A fifth aspect of the present application provides a printed circuit board, which includes the above-mentioned laminate. DETAILED DESCRIPTION

[0031] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below. And the preferred embodiments of the present invention are given. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0032] In addition, the terms "first aspect", "second aspect", "third aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Nor can they be understood as implicitly indicating the importance or number of technical features indicated. Moreover, "first", "second", "third", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0033] In the description of the present invention, “plurality” means at least two, for example, two, three, etc., unless otherwise clearly and specifically defined.

[0034] In the present invention, when a linking site is not specified in a group, it means that any linking site in the group can be used as the linking site.

[0035] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0036] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0037] The terms "include", "comprising", "containing", "having", "having" or other variations herein are intended to encompass non-exclusive inclusions, and no distinction is made between these terms. The term "comprising" means that other steps and ingredients that do not affect the end result may be added. The compositions and methods / processes of the present invention comprise, consist of, and consist essentially of the essential elements and limitations described herein, as well as any additional or optional ingredients, components, steps, or limitations described herein.

[0038] In this article, "DCPD ring" refers to

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0040] The first aspect of the present application provides a modified resin composition, which comprises the following components in parts by weight:

[0041]

[0042] It is understood that, in the present application, the raw materials for preparing the modified allylbenzoxazine prepolymer include allylbenzoxazine resin and allyl compound.

[0043] Among them, the structure of the allyl benzoxazine resin contains allyl benzoxazine, and the allyl benzoxazine can be but is not limited to the following structural formula:

[0044]

[0045] X is independently selected from -CHR1-, -CR2R3-, -SO2-, -O- or DCPD ring;

[0046] R1, R2, and R3 are each independently selected from -H or -CH3.

[0047] In some embodiments of the present application, the allyl compound is a first allyl compound, and its chemical name is: 2,2-bis(4-allyloxyphenyl)hexafluoropropane, and its structure is shown below:

[0048]

[0049] In some embodiments of the present application, the allyl compound includes a first allyl compound and a second allyl compound, and the second allyl compound is selected from one or more of diallyl bisphenol A, diallyl bisphenol S, diallyl bisphenol F, and bisphenol A bisallyl ether.

[0050] In some embodiments of the present application, in the modified allylbenzoxazine prepolymer, the mass ratio of the allylbenzoxazine compound to the allyl compound is 100:(50-100), and examples of the mass ratio include but are not limited to 100:50, 100:55, 100:60, 100:65, 100:70, 100:75, 100:80, 100:85, 100:90, 100:95, 100:100. Preferably, it is 100:(60-80), and more preferably 100:70.

[0051] In some embodiments of the present application, the method for preparing the modified allyl benzoxazine prepolymer comprises the following steps:

[0052] The allyl compound heated to a molten state and the allyl benzoxazine resin are mixed, prepolymerized at 100° C. to 150° C. for 60 minutes to 120 minutes, and cooled to room temperature to obtain a modified allyl benzoxazine prepolymer.

[0053] The temperature for heating after mixing the allyl compound and the allylbenzoxazine resin includes, but is not limited to, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, and 150°C; the reaction prepolymerization time includes, but is not limited to, 60min, 65min, 70min, 75min, 80min, 85min, 90min, 95min, 100min, 105min, 110min, 115min, and 120min. Preferably, the reaction temperature is 110°C to 130°C, and the reaction time is 80min to 100min; more preferably, the reaction temperature is 120°C, and the reaction time is 90min.

[0054] The modified resin composition of the present application adopts an allyl compound and an allylbenzoxazine resin to prepare a modified allylbenzoxazine prepolymer. The prepolymerization method effectively reduces the steric hindrance of the modified resin composition, greatly improves the crosslinking density of the modified resin composition, and can effectively reduce the thermal expansion coefficient of the material and improve the heat resistance of the material.

[0055] In addition, due to the synergistic flame retardant effect of fluorine and nitrogen in the modified allylbenzoxazine prepolymer, the modified resin composition of the present application can achieve the UL94V0 flame retardant grade by adding a small amount of flame retardant, avoiding the negative impact of adding a large amount of flame retardant on the material in the traditional operation method.

[0056] Furthermore, the modified allylbenzoxazine prepolymer is reasonably compatible with the other raw material components in the modified resin composition, so that the modified resin composition has the characteristics of low thermal expansion coefficient, low dielectric properties, low dielectric loss, high heat resistance and high flame retardancy.

[0057] Preferably, the modified resin composition comprises the following components in parts by weight:

[0058]

[0059]

[0060] In some embodiments of the present application, the curing agent is selected from one or more of phenolic resin, dicyandiamide, diaminodiphenyl sulfone, diaminodiphenyl ether, cyanate resin, active ester, anhydride curing agent, benzoxazine, bisphenol, monophenol, polyhydroxyphenol, hydroquinone, and diaminodiphenylmethane.

[0061] In some embodiments of the present application, the cyanate ester resin is selected from one or more of bisphenol A type cyanate ester resin, phenolic cyanate ester resin, bisphenol F type cyanate ester resin, bisphenol S type cyanate ester, biphenyl type cyanate ester, naphthalene structure cyanate ester, multifunctional cyanate ester resin, bisphenol M type cyanate ester resin, bisphenol E type cyanate ester resin, and dicyclopentadiene bisphenol type cyanate ester resin.

[0062] In some embodiments of the present application, the anhydride curing agent is selected from one or more of phthalic anhydride (PA), styrene maleic anhydride copolymer, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, maleic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, tetrahydrophthalic anhydride (4-THPA), benzophenonetetracarboxylic dianhydride, glutaric anhydride, polyazetaic anhydride, dichloromaleic anhydride, trimellitic anhydride, pyromellitic anhydride, pyromellitic anhydride, dibenzophenonetetracarboxylic dianhydride, dodecylmaleic anhydride, succinic anhydride, hexahydrophthalic anhydride, and cyclopentanetetracarboxylic anhydride.

[0063] In some embodiments of the present application, the curing agent is bisphenol A cyanate ester resin.

[0064] In some embodiments of the present application, the functional resin is selected from one or more of epoxy resin, benzoxazine resin, polyphenylene ether resin, hydrocarbon resin and bismaleimide resin.

[0065] In some embodiments of the present application, the epoxy resin is selected from one or more of naphthalene-type epoxy resin, bisphenol A-type epoxy resin, bisphenol F-type epoxy resin, phosphorus-containing epoxy resin, unsaturated epoxy resin, phenolic epoxy resin, o-cresol-formaldehyde epoxy resin, bisphenol A phenolic epoxy resin, multifunctional epoxy resin, alicyclic epoxy resin, resorcinol epoxy resin, rubber-modified epoxy resin, biphenyl epoxy resin, and dicyclopentadiene epoxy resin.

[0066] In some embodiments of the present application, the benzoxazine resin is selected from one or more of bisphenol A-type benzoxazine resin, bisphenol F-type benzoxazine resin, main chain benzoxazine resin, phosphorus-containing benzoxazine, bisphenol S-type benzoxazine resin, dicyclopentadiene benzoxazine resin, biphenyl-type benzoxazine resin, tetraphenol ethane benzoxazine resin, and naphthalene-type benzoxazine resin.

[0067] In some embodiments of the present application, the polyphenylene ether resin is selected from one or more of bishydroxy polyphenylene ether resin, bisvinylbenzyl polyphenylene ether resin, vinylbenzyl modified bisphenol A polyphenylene ether resin, methacrylic polyphenylene ether resin, amino-terminated polyphenylene ether resin, maleimide or maleic anhydride modified polyphenylene ether resin.

[0068] In some embodiments of the present application, the bismaleimide resin is not particularly limited and is selected from an organic compound containing two or more maleimide structures in the molecular structure, and the maleimide structure is selected from N-phenylmaleimide, N-(2-methylphenyl)maleimide, N-(4-methylphenyl)maleimide, N-(2,6-dimethylphenyl)maleimide, di(4-maleimidophenyl)methane, 2,2-bis(4-(4-maleimidophenoxy)-phenyl)propane, di(3,5-dimethyl-4-maleimidophenyl)methane, di(3-ethyl-5-methyl-4-maleimidophenyl)methane, di(3,5-diethyl-4-maleimidophenyl)methane, polyphenylmethane bismaleimide, and one or more maleimide containing biphenyl structure.

[0069] In some embodiments of the present application, the functional resin is a bismaleimide resin and a naphthalene-type epoxy resin.

[0070] In some embodiments of the present application, the above-mentioned inorganic filler is selected from one or more of zirconium vanadate, zirconium tungstate, hafnium tungstate, microcrystalline glass, eucryptite, spherical silica, composite silica, fused silica, quartz, mica powder, titanium dioxide, magnesium oxide, magnesium hydroxide, talc, aluminum oxide, silicon carbide, boron nitride, aluminum nitride, molybdenum oxide, barium sulfate, zinc molybdate, zinc borate, zinc stannate, zinc oxide, strontium titanate, barium titanate, calcium titanate, clay, and kaolin.

[0071] In some embodiments of the present application, the inorganic filler is spherical silica.

[0072] In some embodiments of the present application, the flame retardant is selected from one or more of decabromodiphenylethane, tetrabromobisphenol A, brominated epoxy resin, phosphorus-containing epoxy resin, phosphorus-containing phenolic resin, phosphazene compound, phosphate compound, phosphorus-containing cyanate, and phosphorus-containing benzoxazine.

[0073] In some embodiments of the present application, the curing accelerator is selected from one or more of tertiary amine accelerators, imidazole accelerators, peroxide accelerators, organophosphorus accelerators and transition metal carboxylate accelerators, such as 2-methylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, zinc octanoate, zinc isooctanoate, stannous octanoate, dibutyltin dilaurate, zinc naphthenate, cobalt naphthenate, aluminum acetylacetonate, cobalt acetylacetonate, copper acetylacetonate.

[0074] In some embodiments of the present application, the curing accelerator is 2-methylimidazole.

[0075] The second aspect of the present application provides the use of the modified resin composition in integrated circuit packaging and printed circuit boards.

[0076] The third aspect of the present application provides a prepreg, which includes a reinforcing material and a resin material loaded on the surface of the reinforcing material, wherein the resin material is the modified resin composition mentioned above.

[0077] In some embodiments of the present application, the resin composition is loaded into the reinforcing material by an impregnation method, and heated at 150° C. to 250° C. for 2 min to 10 min to obtain a semi-cured prepreg, ie, a semi-cured sheet.

[0078] In some embodiments of the present application, the reinforcing material is selected from inorganic fiber materials or organic fiber materials. Inorganic fiber materials include but are not limited to glass fiber, carbon fiber, silicon carbide fiber and asbestos fiber. Organic fiber materials include but are not limited to nylon, ultra-high molecular weight polyethylene fiber, aramid fiber, polyimide fiber, polyester fiber and cotton fiber.

[0079] Among them, glass fiber includes different types of glass fiber such as E, NE, D, S, and T.

[0080] A fourth aspect of the present application provides a laminate, wherein raw materials for preparing the laminate include at least one of the above-mentioned prepreg sheets.

[0081] It can be understood that the amount of the prepreg in the raw materials for preparing the above-mentioned laminate can be adjusted according to the actual application.

[0082] In some embodiments of the present application, one side or both sides of the laminate are coated with metal foil. In this case, the laminate is a metal foil-clad laminate.

[0083] It is understandable that the metal foil can be copper foil or aluminum foil, and there is no particular limitation on their thickness, which can be adjusted according to actual applications. Specifically, the metal foil is copper foil, and the thickness of the copper foil is 3 μm to 70 μm, and the laminate is a copper-clad laminate.

[0084] In some embodiments of the present application, the steps for preparing the above-mentioned laminate are as follows:

[0085] At a temperature of 150°C to 300°C and a pressure of 10kgf / cm 2 ~30kgf / cm 2 , vacuum degree <2kPa, hot pressing the above-mentioned semi-cured sheet for 200min to 400min to obtain a laminated board.

[0086] It can be understood that when the raw materials for preparing the laminate include two or more prepregs, the prepregs are stacked and hot-pressed.

[0087] A fifth aspect of the present application provides a printed circuit board, which includes the above-mentioned laminate.

[0088] The above-mentioned printed circuit board has a low thermal expansion coefficient, a low dielectric constant, a low dielectric loss and a high heat resistance, and is suitable for preparing high-performance printed circuit boards such as high temperature resistance and anti-aging, integrated circuit packaging, high frequency and high speed, thereby promoting the development of high-end integrated circuits.

[0089] The present application will be further described in detail below with reference to specific examples. The raw materials, reagents, etc. used in the following examples, unless otherwise specified, can be purchased from commercially available products

[0090] The raw materials used in the synthesis examples, embodiments and comparative examples of this application are as follows:

[0091] Allylbenzoxazine resin, available from Huntsman, model: HZ8298H60.

[0092] Bisphenol A type benzoxazine, available from Huntsman, model: LZ8290H62.

[0093] Bisphenol A cyanate ester, available from Lonza Group, model: BA-230S.

[0094] Bismaleimide resin, available from KI Chemicals, model: BMI-70.

[0095] Diallyl bisphenol A can be purchased from Honghu Shuangma Resin Factory.

[0096] Naphthalene type epoxy resin, available from Nippon Kayaku Co., Ltd., model: NC-7000.

[0097] Flame retardant, available from Daba Chemical, model: PX200.

[0098] Spherical silica, available from Yaduma, model: SC6500-SXD.

[0099] 2-Methylimidazole can be purchased from Shikoku Chemical.

[0100] Synthesis example 1

[0101] The first allyl compound 2,2-bis(4-allyloxyphenyl)hexafluoropropane was prepared, and the structure is shown below:

[0102]

[0103] The specific preparation steps are as follows:

[0104] 1) Hexafluorobisphenol A (0.4 mol, 134.5 g) was placed in a three-necked flask, 300 mL of acetone was added, and the mixture was stirred to completely dissolve the hexafluorobisphenol A. Then, anhydrous potassium carbonate (0.1 mol, 138.2 g) and potassium iodide (3 wt.% hexafluorobisphenol A, 4.035 g) were added to the three-necked flask, and the rotation speed was adjusted to allow the anhydrous potassium carbonate and potassium iodide solids to be suspended in the solution for later use.

[0105] 2) Under nitrogen atmosphere, add allyl bromide (0.1 mol, 120.98 g) to the three-necked flask in 1), stir and reflux at 60° C. for 26 h, and finally monitor the reaction status by spot plate.

[0106] 3) After the reaction is completed, the anhydrous potassium carbonate and potassium iodide solids are removed by suction filtration; the acetone is removed from the liquid by vacuum distillation;

[0107] 4) The liquid obtained after reduced pressure distillation is purified by column chromatography (eluent: pure petroleum ether), and the petroleum ether is removed by rotary evaporation to obtain a colorless oily liquid, which is then dried to obtain the allyl compound 2,2-bis(4-allyloxyphenyl)hexafluoropropane.

[0108] Next, the first allyl compound is applied to the examples to prepare a modified resin compound.

[0109] Example 1

[0110] 1) 70 parts of 2,2-bis(4-allyloxyphenyl)hexafluoropropane were heated to a molten state, 100 parts of allylbenzoxazine resin were added and mixed evenly, and the mixture was prepolymerized at 120° C. for 90 minutes and then cooled to room temperature to obtain a modified allylbenzoxazine prepolymer A.

[0111] 2) 20 parts of the modified allyl benzoxazine prepolymer A, 5 parts of bismaleimide resin, 15 parts of bisphenol A cyanate resin and 10 parts of naphthalene epoxy resin are dissolved in a mixed solvent of butanone, toluene and propylene glycol methyl ether, wherein the mass ratio of butanone, toluene and propylene glycol methyl ether is 1:1:1. Under stirring conditions, 20 parts of spherical silica, 5 parts of flame retardant and 1 part of 2-methylimidazole are added, and stirring is continued to obtain a uniform modified allyl benzoxazine prepolymer resin composition glue.

[0112] 3) 2116 glass fiber cloth (basic weight 105g / m 2 ) was immersed in the modified allyl benzoxazine prepolymer resin composition glue solution, placed in a hot air circulation oven, and baked at 180° C. for 3 minutes to obtain a semi-cured sheet with a resin content of 50%.

[0113] 4) Stack 6 prepregs, cover the upper and lower sides of the stack with an electrolytic copper foil of 18 μm, and place them in a vacuum press with programmable temperature and pressure control. 2 Under the pressure of 220℃*3h, a copper-clad laminate with a thickness of 0.6mm was made.

[0114] Embodiment 2:

[0115] 1) 70 parts of 2,2-bis(4-allyloxyphenyl)hexafluoropropane were heated to a molten state, 100 parts of allylbenzoxazine resin were added and mixed evenly, and the mixture was prepolymerized at 120° C. for 90 minutes and then cooled to room temperature to obtain a modified allylbenzoxazine prepolymer A.

[0116] 2) 35 parts of the modified allyl benzoxazine prepolymer A, 10 parts of bismaleimide resin, 10 parts of bisphenol A cyanate resin and 5 parts of naphthalene epoxy resin are dissolved in a mixed solvent of butanone, toluene and propylene glycol methyl ether, wherein the mass ratio of butanone, toluene and propylene glycol methyl ether is 1:1:1. Under stirring conditions, 30 parts of spherical silica, 10 parts of flame retardant and 5 parts of 2-methylimidazole are added, and stirring is continued to obtain a uniform modified allyl benzoxazine prepolymer resin composition glue.

[0117] 3) 2116 glass fiber cloth (basic weight 105g / m 2 ) was immersed in the modified allyl benzoxazine prepolymer resin composition glue solution, placed in a hot air circulation oven and baked at 180° C. for 3 minutes to obtain a semi-cured sheet with a resin content of 50%.

[0118] 4) Stack 6 prepregs, cover the upper and lower sides of the stack with an electrolytic copper foil of 18 μm, and place them in a vacuum press with programmable temperature and pressure control. 2 Under the pressure of 220℃*3h, a copper-clad laminate with a thickness of 0.6mm was made.

[0119] Embodiment 3:

[0120] 1) 70 parts of 2,2-bis(4-allyloxyphenyl)hexafluoropropane were heated to a molten state, 100 parts of allylbenzoxazine resin were added and mixed evenly, and the mixture was prepolymerized at 120° C. for 90 minutes and then cooled to room temperature to obtain a modified allylbenzoxazine prepolymer A.

[0121] 2) 50 parts of the modified allyl benzoxazine prepolymer A, 5 parts of bismaleimide resin, 20 parts of bisphenol A cyanate resin and 20 parts of naphthalene epoxy resin are dissolved in a mixed solvent of butanone, toluene and propylene glycol methyl ether, wherein the mass ratio of butanone, toluene and propylene glycol methyl ether is 1:1:1. Under stirring conditions, 40 parts of spherical silica, 10 parts of flame retardant and 10 parts of 2-methylimidazole are added, and stirring is continued to obtain a uniform modified allyl benzoxazine prepolymer resin composition glue.

[0122] 3) 2116 glass fiber cloth (basic weight 105g / m 2 ) was immersed in the modified allyl benzoxazine prepolymer resin composition glue solution, placed in a hot air circulation oven and baked at 180° C. for 3 minutes to obtain a semi-cured sheet with a resin content of 50%.

[0123] 4) Stack 6 prepregs, cover the upper and lower sides of the stack with an electrolytic copper foil of 18 μm, and place them in a vacuum press with programmable temperature and pressure control. 2 Under the pressure of 220℃*3h, a copper-clad laminate with a thickness of 0.6mm was made.

[0124] Embodiment 4:

[0125] 1) 50 parts of 2,2-bis(4-allyloxyphenyl)hexafluoropropane and 20 parts of allyl bisphenol A are heated to a molten state, 100 parts of allyl benzoxazine resin are added and mixed evenly, and the mixture is prepolymerized at 120° C. for 90 minutes and then cooled to room temperature to obtain a modified allyl benzoxazine prepolymer B.

[0126] 2) 50 parts of the modified allyl benzoxazine prepolymer B, 10 parts of bismaleimide resin, 10 parts of bisphenol A cyanate resin and 10 parts of naphthalene epoxy resin are dissolved in a mixed solvent of butanone, toluene and propylene glycol methyl ether, wherein the mass ratio of butanone, toluene and propylene glycol methyl ether is 1:1:1. Under stirring, 20 parts of spherical silica, 5 parts of flame retardant and 5 parts of 2-methylimidazole are added, and stirring is continued to obtain a uniform modified allyl benzoxazine prepolymer resin composition glue.

[0127] 3) 2116 glass fiber cloth (basic weight 105g / m 2 ) was immersed in the modified allyl benzoxazine prepolymer resin composition glue solution, placed in a hot air circulation oven and baked at 180° C. for 3 minutes to obtain a semi-cured sheet with a resin content of 50%.

[0128] 4) Stack 6 prepregs, cover the upper and lower sides of the stack with an electrolytic copper foil of 18 μm, and place them in a vacuum press with programmable temperature and pressure control. 2 Under the pressure of 220℃*3h, a copper-clad laminate with a thickness of 0.6mm was made.

[0129] Embodiment 5:

[0130] 1) 70 parts of 2,2-bis(4-allyloxyphenyl)hexafluoropropane were heated to a molten state, 100 parts of allylbenzoxazine resin were added and mixed evenly, and the mixture was prepolymerized at 120° C. for 90 minutes and then cooled to room temperature to obtain a modified allylbenzoxazine prepolymer A.

[0131] 2) 50 parts of the modified allyl benzoxazine prepolymer A, 5 parts of bismaleimide resin, 20 parts of bisphenol A cyanate resin and 20 parts of naphthalene epoxy resin are dissolved in a mixed solvent of butanone, toluene and propylene glycol methyl ether, wherein the mass ratio of butanone, toluene and propylene glycol methyl ether is 1:1:1. Under stirring, 30 parts of spherical silica, 10 parts of flame retardant and 10 parts of 2-methylimidazole are added, and stirring is continued to obtain a uniform modified allyl benzoxazine prepolymer resin composition glue.

[0132] 3) 2116 glass fiber cloth (basic weight 105g / m 2 ) was immersed in the modified allyl benzoxazine prepolymer resin composition glue solution, placed in a hot air circulation oven and baked at 180° C. for 3 minutes to obtain a semi-cured sheet with a resin content of 50%.

[0133] 4) Stack 6 prepregs, cover the upper and lower sides of the stack with an electrolytic copper foil of 18 μm, and place them in a vacuum press with programmable temperature and pressure control. 2 Under the pressure of 220℃*3h, a copper-clad laminate with a thickness of 0.6mm was made.

[0134] Embodiment 6:

[0135] 1) 70 parts of 2,2-bis(4-allyloxyphenyl)hexafluoropropane were heated to a molten state, 100 parts of allylbenzoxazine resin were added and mixed evenly, and the mixture was prepolymerized at 120° C. for 90 minutes and then cooled to room temperature to obtain a modified allylbenzoxazine prepolymer A.

[0136] 2) 60 parts of the modified allyl benzoxazine prepolymer A, 10 parts of bismaleimide resin, 20 parts of bisphenol A cyanate resin and 10 parts of naphthalene epoxy resin are dissolved in a mixed solvent of butanone, toluene and propylene glycol methyl ether, wherein the mass ratio of butanone, toluene and propylene glycol methyl ether is 1:1:1. Under stirring conditions, 35 parts of spherical silica, 5 parts of flame retardant and 5 parts of 2-methylimidazole are added, and stirring is continued to obtain a uniform modified allyl benzoxazine prepolymer resin composition glue.

[0137] 3) 2116 glass fiber cloth (basic weight 105g / m 2 ) was immersed in the modified allyl benzoxazine prepolymer resin composition glue solution, placed in a hot air circulation oven and baked at 180° C. for 3 minutes to obtain a semi-cured sheet with a resin content of 50%.

[0138] Six prepregs were stacked, and an electrolytic copper foil with a thickness of 18 μm was covered on each of the upper and lower surfaces of the stack. The stack was placed in a programmable temperature and pressure controlled vacuum press and heated to 30 kgf / cm2 in a vacuum state. 2 Under the pressure of 220℃*3h, a copper-clad laminate with a thickness of 0.6mm was made.

[0139] Example 7: 1) 70 parts of 2,2-bis(4-allyloxyphenyl)hexafluoropropane were heated to a molten state, 100 parts of allylbenzoxazine resin were added and mixed evenly, and the mixture was prepolymerized at 120° C. for 90 min and then cooled to room temperature to obtain a modified allylbenzoxazine prepolymer A.

[0140] 2) 70 parts of the modified allyl benzoxazine prepolymer A, 10 parts of bismaleimide resin, 20 parts of bisphenol A cyanate resin and 10 parts of naphthalene epoxy resin are dissolved in a mixed solvent of butanone, toluene and propylene glycol methyl ether, wherein the mass ratio of butanone, toluene and propylene glycol methyl ether is 1:1:1. Under stirring, 40 parts of spherical silica, 5 parts of flame retardant and 5 parts of 2-methylimidazole are added, and stirring is continued to obtain a uniform modified allyl benzoxazine prepolymer resin composition glue.

[0141] 3) 2116 glass fiber cloth (basic weight 105g / m 2 ) was immersed in the modified allyl benzoxazine prepolymer resin composition glue solution, placed in a hot air circulation oven and baked at 180° C. for 3 minutes to obtain a semi-cured sheet with a resin content of 50%.

[0142] Six prepregs were stacked, and an electrolytic copper foil with a thickness of 18 μm was covered on each of the upper and lower surfaces of the stack. The stack was placed in a programmable temperature and pressure controlled vacuum press and heated to 30 kgf / cm2 in a vacuum state. 2Under the pressure of 220℃*3h, a copper-clad laminate with a thickness of 0.6mm was made.

[0143] Embodiment 8:

[0144] 1) 70 parts of 2,2-bis(4-allyloxyphenyl)hexafluoropropane were heated to a molten state, 100 parts of allylbenzoxazine resin were added and mixed evenly, and the mixture was prepolymerized at 120° C. for 90 minutes and then cooled to room temperature to obtain a modified allylbenzoxazine prepolymer A.

[0145] 2) 50 parts of the modified allyl benzoxazine prepolymer A, 5 parts of bismaleimide resin, 20 parts of bisphenol A cyanate resin and 20 parts of naphthalene epoxy resin are dissolved in a mixed solvent of butanone, toluene and propylene glycol methyl ether, wherein the mass ratio of butanone, toluene and propylene glycol methyl ether is 1:1:1. Under stirring, 20 parts of spherical silica, 10 parts of flame retardant and 10 parts of 2-methylimidazole are added, and stirring is continued to obtain a uniform modified allyl benzoxazine prepolymer resin composition glue.

[0146] 3) 2116 glass fiber cloth (basic weight 105g / m 2 ) was immersed in the modified allyl benzoxazine prepolymer resin composition glue solution, placed in a hot air circulation oven and baked at 180° C. for 3 minutes to obtain a semi-cured sheet with a resin content of 50%.

[0147] 4) Stack 6 prepregs, cover the upper and lower sides of the stack with an electrolytic copper foil of 18 μm, and place them in a vacuum press with programmable temperature and pressure control. 2 Under the pressure of 220℃*3h, a copper-clad laminate with a thickness of 0.6mm was made.

[0148] Embodiment 9:

[0149] 1) 70 parts of 2,2-bis(4-allyloxyphenyl)hexafluoropropane were heated to a molten state, 100 parts of allylbenzoxazine resin were added and mixed evenly, and the mixture was prepolymerized at 120° C. for 90 minutes and then cooled to room temperature to obtain a modified allylbenzoxazine prepolymer A.

[0150] 2) 50 parts of the modified allyl benzoxazine prepolymer A, 10 parts of bismaleimide resin, 20 parts of bisphenol A cyanate resin and 20 parts of naphthalene epoxy resin are dissolved in a mixed solvent of butanone, toluene and propylene glycol methyl ether, wherein the mass ratio of butanone, toluene and propylene glycol methyl ether is 1:1:1. Under stirring conditions, 40 parts of spherical silica, 10 parts of flame retardant and 10 parts of 2-methylimidazole are added, and stirring is continued to obtain a uniform modified allyl benzoxazine prepolymer resin composition glue.

[0151] 3) 2116 glass fiber cloth (basic weight 105g / m 2 ) was immersed in the modified allyl benzoxazine prepolymer resin composition glue solution, placed in a hot air circulation oven and baked at 180° C. for 3 minutes to obtain a semi-cured sheet with a resin content of 50%.

[0152] 4) Stack 6 prepregs, cover the upper and lower sides of the stack with an electrolytic copper foil of 18 μm, and place them in a vacuum press with programmable temperature and pressure control. 2 Under the pressure of 220℃*3h, a copper-clad laminate with a thickness of 0.6mm was made.

[0153] Comparative Example 1:

[0154] 1) 70 parts of allyl bisphenol A were heated to a molten state, 100 parts of allyl benzoxazine resin were added and mixed evenly, and the mixture was prepolymerized at 120° C. for 90 minutes and then cooled to room temperature to obtain a modified allyl benzoxazine prepolymer C.

[0155] 2) 50 parts of the modified allyl benzoxazine prepolymer C, 5 parts of bismaleimide resin, 20 parts of bisphenol A cyanate resin and 20 parts of naphthalene epoxy resin are dissolved in a mixed solvent of butanone, toluene and propylene glycol methyl ether, wherein the mass ratio of butanone, toluene and propylene glycol methyl ether is 1:1:1. Under stirring conditions, 20 parts of spherical silica, 10 parts of flame retardant and 10 parts of 2-methylimidazole are added, and stirring is continued to obtain a uniform modified allyl benzoxazine prepolymer resin composition glue.

[0156] 3) 2116 glass fiber cloth (basic weight 105g / m 2 ) was immersed in the modified allyl benzoxazine prepolymer resin composition glue solution, placed in a hot air circulation oven and baked at 180° C. for 3 minutes to obtain a semi-cured sheet with a resin content of 50%.

[0157] 4) Stack 6 prepregs, cover the upper and lower sides of the stack with an electrolytic copper foil of 18 μm, and place them in a vacuum press with programmable temperature and pressure control.2 Under the pressure of 220℃*3h, a copper-clad laminate with a thickness of 0.6mm was made.

[0158] Comparative Example 2:

[0159] 1) 50 parts of bisphenol A benzoxazine, 10 parts of bismaleimide resin, 20 parts of bisphenol A cyanate resin and 20 parts of naphthalene epoxy resin are dissolved in a mixed solvent of butanone, toluene and propylene glycol methyl ether, wherein the mass ratio of butanone, toluene and propylene glycol methyl ether is 1:1:1. Under stirring conditions, 40 parts of spherical silica, 10 parts of flame retardant and 10 parts of 2-methylimidazole are added, and stirring is continued to obtain a uniform benzoxazine resin composition glue.

[0160] 2) 2116 glass fiber cloth (basic weight 105g / m 2 ) was immersed in the above-mentioned benzoxazine resin composition glue solution, placed in a hot air circulation oven and baked at 180° C. for 3 minutes to obtain a semi-cured sheet with a resin content of 50%.

[0161] 3) Stack 6 prepregs, cover the upper and lower sides of the stack with an electrolytic copper foil of 18 μm, and place them in a programmable temperature and pressure controlled vacuum press. 2 Under the pressure of 220℃*3h, a copper-clad laminate with a thickness of 0.6mm was made.

[0162] Comparative Example 3

[0163] 1) 50 parts of bisphenol A type benzoxazine, 10 parts of bismaleimide resin, 20 parts of bisphenol A type cyanate resin and 20 parts of naphthalene type epoxy resin are dissolved in a mixed solvent of butanone, toluene and propylene glycol methyl ether in sequence, wherein the mass ratio of butanone, toluene and propylene glycol methyl ether is 1:1:1. Under stirring conditions, 40 parts of spherical silica, 10 parts of flame retardant and 10 parts of 2-methylimidazole are added, and stirring is continued to obtain a uniform modified allyl benzoxazine prepolymer resin composition glue.

[0164] 2) 2116 glass fiber cloth (basic weight 105g / m 2 ) was immersed in the modified allyl benzoxazine prepolymer resin composition glue solution, placed in a hot air circulation oven and baked at 180° C. for 3 minutes to obtain a semi-cured sheet with a resin content of 50%.

[0165] 3) Stack 6 prepregs, cover the upper and lower sides of the stack with an electrolytic copper foil of 18 μm, and place them in a vacuum press with programmable temperature and pressure control. 2Under the pressure of 220℃*3h, a copper-clad laminate with a thickness of 0.6mm was made.

[0166] The formulas and process parameters of Examples 1-9 and Comparative Examples 1-3 are summarized in Table 1.

[0167] Table 1

[0168]

[0169] The copper-clad laminates prepared in Examples 1-9 and Comparative Examples 1-3 were tested for performance, and the results are shown in Table 2 below:

[0170] Table 2

[0171]

[0172] The test method is as follows:

[0173] 1) Peel strength: The test method is carried out in accordance with IPC-TM-650 2.4.8;

[0174] 2) Glass transition temperature (Tg): tested according to IPC-TM650 2.4.25D;

[0175] 3) Flame retardant grade: tested according to IPC-TM650 2.3.10;

[0176] 4) Water absorption: Tested according to IPC-TM650 2.6.2.1;

[0177] 5) Dielectric constant (Dk) and dielectric loss factor (Df): tested according to IPC-TM650 2.5.5.2;

[0178] 6) CTE thermal expansion performance test: tested according to IPC-TM650 2.4.24;

[0179] 7)T300 heat resistance: tested according to IPC-TM650 2.4.24.

[0180] From the test results in Table 2 above, it can be seen that the copper-clad laminate prepared by the modified resin composition provided in the embodiment of the present invention has low thermal expansion coefficient, low dielectric constant, low dielectric loss and high heat resistance, and also has low water absorption. Comparison of Examples 1 to 3 and 5 to 7 shows that within a certain range, for example 20 to 70 parts, as the content of the modified allyl benzoxazine prepolymer component changes, the thermal expansion coefficient of the obtained material first decreases and then increases. Comparison of Examples 4 and 8 with Comparative Example 1 shows that by changing the composition ratio of the modified allyl benzoxazine prepolymer, as the content of the first allyl compound in the allyl compound of the prepolymer composition raw material decreases, the heat resistance of the obtained material becomes worse and the linear expansion coefficient becomes higher.

[0181] Compared with Example 9, Comparative Examples 2 and 3 respectively use the same content of bisphenol A-type benzoxazine and allyl benzoxazine resin to replace the modified allyl benzoxazine prepolymer A, and the heat resistance of the obtained materials becomes worse and the linear expansion coefficient becomes higher.

[0182] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0183] The above-described embodiments only express several implementation methods of the present invention, which are convenient for understanding the technical solutions of the present invention in detail, but they cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided by the present invention are all within the protection scope of the claims attached to the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the contents of the attached claims, and the description can be used to interpret the contents of the claims.

Claims

1. A modified resin composition, characterized in that According to the mass percentage, it includes the following components: The raw materials for preparing the modified allylbenzoxazine prepolymer include allylbenzoxazine resin and allyl compound; The allyl compound includes a first allyl compound, and the first allyl compound is 2,2-bis(4-allyloxyphenyl)hexafluoropropane.

2. The modified resin composition according to claim 1, characterized in that The mass ratio of the allylbenzoxazine resin to the allyl compound is 100:(50-100).

3. The modified resin composition according to claim 1, characterized in that The structure of the allylbenzoxazine resin includes allyl benzoxazine, and the allyl benzoxazine is selected from one or more of the following structures: Wherein, X is selected from -CHR1-, -CR2R3-, -SO2-, -O- or DCPD ring; R1, R2, and R3 are each independently selected from -H or -CH3.

4. The modified resin composition according to claim 1, characterized in that The method for preparing the modified allylbenzoxazine prepolymer comprises the following steps: The allyl compound and the allylbenzoxazine resin are mixed and reacted at 100° C. to 150° C. for 60 min to 120 min to obtain the modified allylbenzoxazine prepolymer.

5. The modified resin composition according to any one of claims 1 to 4, characterized in that: According to the mass percentage, it includes the following components:

6. A prepreg, comprising a reinforcing material and a resin material loaded on the reinforcing material, characterized in that: The resin material is the modified resin composition according to any one of claims 1 to 5.

7. A laminated board, characterized in that: The raw materials for preparing the laminate include the prepreg as claimed in claim 6.

8. A printed circuit board, characterized in that: The printed wiring board comprises the laminate according to claim 7.

Citation Information

Patent Citations

  • Allyl flame-retardant prepolymer, resin composition, composite resin, prepreg and laminated board

    CN114316115A